2020
DOI: 10.1002/cplu.202000567
|View full text |Cite
|
Sign up to set email alerts
|

Anion Receptors for the Discrimination of ATP and ADP in Biological Media

Abstract: The design and synthesis of molecular receptors for the selective binding of nucleoside phosphate anions (e. g. ATP, ADP, GTP, GDP, UDP) in aqueous media at physiological pH is a valuable research endeavour, which could lead to new sensing tools for biomedical and drug discovery research. However, this target is very challenging due to similarities in anion size, structure and charge. This Minireview provides an account of the development of receptors capable of discriminating between ATP and ADP, and their ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 58 publications
(96 reference statements)
0
16
1
Order By: Relevance
“…Crucially, the sensing selectivity of the receptors follows the order AMP > ADP > ATP, which is opposite to that observed for most nucleoside phosphate receptors 6–8 where the binding is governed predominantly by electrostatic interactions and thus favours ATP and ADP over AMP. We have previously shown that ATP and ADP prefer to adopt a bidentate binding mode in more conformationally flexible macrocyclic Ln( iii ) receptors.…”
Section: Resultscontrasting
confidence: 67%
See 3 more Smart Citations
“…Crucially, the sensing selectivity of the receptors follows the order AMP > ADP > ATP, which is opposite to that observed for most nucleoside phosphate receptors 6–8 where the binding is governed predominantly by electrostatic interactions and thus favours ATP and ADP over AMP. We have previously shown that ATP and ADP prefer to adopt a bidentate binding mode in more conformationally flexible macrocyclic Ln( iii ) receptors.…”
Section: Resultscontrasting
confidence: 67%
“…5 Adenosine monophosphate (AMP) represents a valuable yet very difficult target for supramolecular detection because of its similarities with the more negatively charged anions, ATP and ADP. 6–8…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Nucleoside phosphate anions are critical to the maintenance of life and play crucial roles in energy transduction, cellular signalling and membrane trans port. 6,7 We have developed a new class of emissive europium complexes bearing arms that bind selectively to ATP and ADP through a combination of electrostatic and hydrogen bonding interactions. Our lead molecule is capable of realtime anal ysis of kinase enzyme activity by monitoring the production of ADP, thereby providing a convenient luminescence assay for screening of potential kinase inhibitors.…”
Section: Synform Could You Tell Us More About Your Group's Areas Of Research and Your Aims?mentioning
confidence: 99%